Appeals to “Normality” and “Common Sense” in the Face of Global Uncertainty: An Interdisciplinary Discourse-Historical Approach - Wodak, Ruth (Informal Logic, 2024)
Crises cause fear, panic, uncertainty, and helplessness. Uncertainty and insecurity challenge everyone involved; everyone expects instructions, planning, explanations and security. However, we confront scaremongering, simplifications, a range of legitimation strategies and fallacies. Specifically, the fallacies are often placed before community, national or even local interests. These developments are illustrated with a detailed qualitative and quantitative discourse analysis of debates in Austria, in the summer of 2023. I argue that the fallacious appeals to common sense and normality depend on their context, with different content, functions, and effects being observable. Such appeals instrumentalize a ‘politics of emotions’ in different ways. Thus, a novel political logic is normalized, superseding rational discourse, deliberation, and expert-led policy formulation.